Interaksi Simbolik dan Pemenuhan Kebutuhan Sosial Di Komunitas Discord Genshin Impact - Subhan Widiansyah; Sauqi Ichsan Kamil (Universitas Halu Oleo (UHO), 2026)
This study aims to analyze how symbolic interaction is formed within the online community of Genshin Impact players and how such interactions contribute to fulfilling the social needs of its members. In the digital era, online communities function not only as platforms for sharing information but also as social arenas where individuals construct identity, intimacy, and shared meaning through digital communication symbols. This research employs a descriptive qualitative approach, using in-depth interviews with five purposively selected informants and observations of community activities on platforms such as Discord. Data analysis follows the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that interactions within the community are constructed through linguistic symbols, emojis, GIFs, voice chat, and community-specific jargon such as “whenyah” and “istri gua.” These symbols function not only as communication tools but also as means of establishing digital identity and social closeness. Furthermore, the community plays a role in fulfilling members’ social needs, including affiliation, emotional support, information, entertainment, and identity expression. Thus, online communities serve as significant digital social spaces for building relationships and fulfilling individuals’ social needs. These findings indicate that digital communities play an important role as modern social arenas, where communication symbols serve as the primary medium for constructing meaning, identity, and fulfilling the social needs of community members.